AVALIAÇÃO DO EFEITO TIPO-ANSIOLÍTICO E TIPO-ANTIDEPRESSIVO DE NANOCÁPSULAS CONTENDO PALMITATO DE ASCORBILA EM CAMUNDONGOS - Ferreira, Carla Fontoura (2013)
Depression and anxiety are psychiatric disorders and present psychological, behavioral and physiological symptoms. As for anxiety and depression treatment, the major problem found is the deficiency on drugs that associate the high effectiveness, high bioavailability and low side effects. Therefore, the L-ascorbil-6-palmitato (PA) associated with nanoparticles could be an inovative alternative for these disorders treatment. In this context, the objective of this study was to evaluate the antidepressant- and anxiolytic-like effects of AP-loaded nanocapsules in different depression and anxiety models on mice. Moreover, we verified the involvement of Na+, K+ -ATPase activity in brain. Animals were divided in 3 groups; group I: control; group II: nano and group III: free. Animals were pretreated intragastrically (i.g) by 24, 48, 72 or 96 hours before of behavioral tests. Group I were pretreated with suspensions containing blank nanocapsules, group II received AP-loaded nanocapsules (30 mg/kg) and group III received free PA (30 mg/kg). In order to evaluate animals locomotor and exploratory activity it was taken the open field test. The forced swimming and tail suspension tests ware used in order to evaluate the antidepressive-type effect, while the elevated plus maze and light/dark box tests were used in order to verify the anxiolytic-type effect. After behavioral tests, animals were killed and brains were removed to determinate Na+, K+ -ATPase activity. Results showed that pretreatment of 24 from 96 hours with AP-loaded nanocapsules reduced the immobility time in forced swim, while free PA in reduced the immobility time with 24 and 48 hours of pretreatment. In the tail suspension tests, AP-loaded nanocapsules and free form reduced the immobility time of 24 to 96 hours of pretreatment. In the elevated plus maze, there was an increase of the number of jump in the pretreated of 48 hours with AP-loaded nanocapsules. No change was observed in the other parameters and groups in this test. In the light/dark box test, all time of pretreatment with AP-loaded nanocapsules increased the latency time for the first entry in the dark compartment and time that the animal remained in the light compartment. Furthermore, no change was found in the Na+, K+-ATPase activity in brains of mice. In the open field test there was no change in animals locomotor and exploratory activity in any of the times tested and groups analyzed. Therefore, we concluded that the AP-loaded nanocapsules showed anxiolytic-like effect. Moreover, AP-loaded nanocapsules and free form presented antidepressant-like effect, but the effect of nanocapsules was more prolonged. Na+, K+-ATPase activity was not involved in the pharmacological effects.